System of performance indicators of logistics inventory management of retail trade enterprises - S. Sharokhina (Вестник университета, 2023)
The article argues that the inventory category is one of the most important categories of logistics, which determines the objective need to conduct a study of the problems of inventory management and the implementation of a logistics concept. The emphasis is placed on the fact that the object of logistics study are material and related information flows, which, according to the logistics concept, are coordinated and managed between the source of supply and the end user within a single system. The logistics system of a trading enterprise is considered in the form of the following main subsystems: purchase, production and marketing. It is proposed from a logistical point of view to consider not the processes of marketing, production and supply themselves, but the movement of flows that arises in these processes. In this regard, the article proposes the system of performance indicators of logistics management inventory of retail trade enterprises.